The SAGE handbook of current developments in grounded theory - Bryant, Antony; Charmaz, Kathy, 1939- (London : SAGE Publications Ltd, 2019)
Building on the success of the bestselling The SAGE Handbook of Grounded Theory (2007), this title provides a much-needed and up-to-date overview, integrating some revised and updated chapters with new ones exploring recent developments in grounded theory and research methods in general. The highly acclaimed editors have once again brought together a team of key academics from a wide range of disciplines, perspectives and countries. This is a method-defining resource for advanced students and researchers across the social sciences. Chapters are arranged around the following parts: Part One: The Grounded Theory Method: 50 Years On; Part Two: Theories and Theorizing in Grounded Theory; Part Three: Grounded Theory in Practice; Part Four: Reflections on Using and Teaching Grounded Theory; Part Five: GTM and Qualitative Research Practice; Part Six: GT Researchers and Methods in Local and Global Worlds.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Grounded theory -- Handbooks, manuals, etc; Qualitative research -- Handbooks, manuals, etc